PENERAPAN MULTIMEDIA KIT DAN MODEL PEMBELAJARAN KONTEKSTUAL MATA PELAJARAN MENEMUKAN PELUANG BARU DARI PELANGGAN UNTUK MENINGKATKAN HASIL BELAJAR KELAS XI PEMASARAN DI SMK NEGERI 1 SUKOHARJO TAHUN PELAJARAN 2015/2016 - Yusuf Teja Ismaya; Harini Harini; Jonet Ariyanto Nugroho (BISE: Jurnal Pendidikan Bisnis dan Ekonomi, 2018)
The aim of this research is to improve the learning achievement of the subject New Opportunity Finding from Customer of XI Marketing Class 3 in SMK Negeri 1 Sukoharjo 2015/2016 academic year through the implementation of multimedia kit and contextual learning model.This research is a classroom action research (CAR). The research has done by a collaboration between the researcher and the teacher of the subject New Opportunity Finding from Customer. The subject of this research is the students of XI Marketing 3 Class in SMK Negeri 1 Sukoharjo which consisted of 36 students. The technique of collecting the data has done by using observation, test, documentation, and interview. The research procedures are planning, acting, observing, and reflecting.Based on the research which has done, it can be concluded that the implementation of multimedia kit and contextual learning model can improve the students’ learning achievement of XI Marketing 3 class. It can be seen in the 1st cycle until the 2nd cycle, the students’ learning achievement showed an improvement. Before the implementation of multimedia kit and contextual learning model, the average score of the students’ learning achievement in the pre-observation was 80 with the passing grade was 61%. Meanwhile in the 1st cycle, the average score of the students’ learning achievement was 82 with the passing grade was 94% and the average score of the students’ learning achievement in the 2nd cycle was 90 with the passing grade was 100%.The conclusion of this research is that the implementation of multimedia kit and contextual learning model can improve the learning achievement of the subject New Opportunity Finding from Customer of XI Marketing Class 3 in SMK Negeri 1 Sukoharjo 2015/2016 academic year.